Landscape of TB Infection and Prevention among People Living with HIV - Anca Vasiliu; Rebecca Abelman; Yousra Kherabi; Antonia Morita Iswari Saktiawati; Alexander Kay (Pathogens, 2022)
Tuberculosis (TB) is one of the leading causes of mortality in people living with HIV (PLHIV) and contributes to up to a third of deaths in this population. The World Health Organization guidelines aim to target early detection and treatment of TB among PLHIV, particularly in high-prevalence and low-resource settings. Prevention plays a key role in the fight against TB among PLHIV. This review explores TB screening tools available for PLHIV, including symptom-based screening, chest radiography, tuberculin skin tests, interferon gamma release assays, and serum biomarkers. We then review TB Preventive Treatment (TPT), shown to reduce the progression to active TB and mortality among PLHIV, and available TPT regimens. Last, we highlight policy-practice gaps and barriers to implementation as well as ongoing research needs to lower the burden of TB and HIV coinfection through preventive activities, innovative diagnostic tests, and cost-effectiveness studies.